Energy Dissipation-Based Method for Strength Determination of Rock under Uniaxial Compression - M. M. He; F. Pang; H. T. Wang; J. W. Zhu; Y. S. Chen (Shock and Vibration)
The energy conversion in rocks has an important significance for evaluation of the stability and safety of rock engineering. In this paper, some uniaxial compression tests for fifteen different rocks were performed. The evolution characteristics of the total energy, elastic energy, and dissipated energy for the fifteen rocks were studied. The dissipation energy coefficient was introduced to study the evolution characteristics of rock. The evolution of the dissipation energy coefficient for different rocks was investigated. The linear interrelations of the dissipation energy coefficients and the yield strength and peak strength were explored. The method was proposed to determine the strength of rock using the dissipation energy coefficients. The results show that the evolution of the dissipation energy coefficient exhibits significant deformation properties of rock. The dissipation energy coefficients linearly increase with the compaction strength, but decrease with the yield strength and peak strength. Moreover, the dissipation energy coefficient can be used to determine the rock burst proneness and crack propagation in rocks.